Social movements and activism in the USA - Valocchi, Stephen M., 1956- (Routledge, 2010)
Social Movements and Activism puts 'front and center' the stories, rhetoric, and emotions of progressive activists from Hartford Connecticut, a post-industrial city in neo-liberal nation. Resisting the impulse to flatten the myriad voices of activism but refusing to leave these voices without context, Social Movements and Activism uses analytic concepts from social movement theory to assist these activists in telling us who they are, why and how they do activism, and what conflicts, tensions, and satisfactions they derive from it.